Negotiating in Silence: Experiences with Parental Leave in Academia - Weststar, Johanna (Relations industrielles / Industrial Relations, 2012)
This paper presents a case study of pregnancy/parental leave arrangements among faculty members at a mid-sized Canadian University from 2000-2010. The data show that leave arrangements were very inconsistent across faculties, across and within departments, and even for individual faculty members who had taken more than one leave. The majority of problematic cases were instances where a faculty member began or ended a leave in the middle of an academic term. Without specific language in their collective agreement, these faculty members often negotiated circumstances that carried individual penalties for duties that were unassigned in light of the leave. This research has implications for unions who must be particularly vigilant and active in professional environments where individual negotiation takes place and union consciousness is lower. It also emphasizes the burden placed on parents when the bearing and rearing of children is framed as an individual right rather than an issue of social reproduction. The paper uses data from a sample of collective agreements across Canadian universities to make recommendations to clarify the procedures for pregnancy and parental leave.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Colleges & universities; Labor Unions; Labor relations; Maternity & paternity leaves; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; University faculty